Aramid fiber III / PTFE self-lubricating fabric grey cloth, self-lubricating liner composite material and preparation method and application of aramid fiber III / PTFE self-lubricating fabric grey cloth
By using aramid III/PTFE fabric with a high cycle number in the self-lubricating liner fabric and combining it with the resin liquid, the problem of insufficient bearing capacity and friction wear performance of the existing self-lubricating liner under high-frequency friction conditions is solved, and higher bearing capacity and better friction wear performance are achieved.
Patent Information
- Application Number
- CN202510029056.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing self-lubricating padding fabrics have small load capacity and poor friction and wear performance under high-frequency friction conditions, making it difficult to adapt to high-frequency friction conditions.
Aramid III fiber filaments and polytetrafluoroethylene fiber filaments were woven to prepare an aramid III/PTFE self-lubricating fabric with a tissue cycle of 4 to 8, and then impregnated in the resin liquid and bonded to the surface of the metal substrate for curing to form a self-lubricating pad composite material.
The self-lubricating pads are improved in load-bearing capacity and friction-resistant wear performance, so that they can adapt to high-frequency friction conditions, and exhibit a lower coefficient of friction and a small wear mark depth under high load and high-speed friction conditions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles and self-lubricating pads, and in particular to an aramid III / PTFE self-lubricating fabric grey cloth, a self-lubricating pad composite material, and a preparation method and application thereof. Background Art
[0002] Self-lubricating cushion fabric is a special cushion material, which is based on fabric and combines self-lubricating components with fabric fibers through a special process. It can automatically provide lubrication function during use and reduce friction and wear between two contact surfaces.
[0003] The common weave structures of self-lubricating cushion fabrics are plain, twill and satin (called the three original weaves), such as 1 / 1 plain, 1 / 2 twill, 2 / 1 twill, 2 / 2 twill, 1 / 3 twill, 3 / 1 twill and the "satin weave" (called broken twill) evolved from the above twill weaves. The characteristics of these weaves are that the surface of the fabric rich in polytetrafluoroethylene fibers is used as the friction working surface on the basis of the original weave structure, and the other side is made of fibers with higher strength and better adhesion as the bonding surface. At present, the weave cycle number of self-lubricating cushion fabrics is mostly ≤4, the weave point fly number is mostly +1, and the weave point fly number of a very small number of twill changes is +2. The self-lubricating cushion fabric of this structure has a small bearing capacity, poor friction and wear performance, and is difficult to adapt to high-frequency friction conditions. Summary of the invention
[0004] In view of this, the present invention provides an aramid III / PTFE self-lubricating fabric grey cloth, a self-lubricating pad composite material, and a preparation method and application thereof. The aramid III / PTFE self-lubricating fabric grey cloth and the self-lubricating pad composite material provided by the present invention have high bearing capacity, good friction and wear resistance, and can adapt to high-frequency friction conditions.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for preparing an aramid III / PTFE self-lubricating fabric grey cloth comprises the following steps:
[0007] Aramid III fiber filaments and polytetrafluoroethylene fiber filaments are used as raw materials for weaving to obtain the aramid III / PTFE self-lubricating fabric grey cloth;
[0008] The number of tissue cycles of the aramid III / PTFE self-lubricating fabric is R, wherein 4≤R≤8;
[0009] The tissue point flying number of the aramid III / PTFE self-lubricating fabric is S, wherein -(R-1)≤S≤+(R-1);
[0010] The warp number of the aramid III / PTFE self-lubricating fabric is S j , the number of latitudinal flights is S w , where |S j |≥|S w |.
[0011] Preferably, the aramid III fiber filament is a multifilament composed of 30 to 150 fiber monofilaments; the linear density of the aramid III fiber filament is 5 tex to 92 tex, and the tensile strength is greater than 20 cN / dtex;
[0012] The polytetrafluoroethylene fiber filament is a multifilament composed of 10 to 100 fiber monofilaments; the linear density of the polytetrafluoroethylene fiber filament is 10 tex to 89 tex, and the tensile strength is greater than 1.35 cN / dtex.
[0013] Preferably, the polytetrafluoroethylene fiber filaments are sized before weaving; the sizing liquid comprises polyvinyl alcohol, an antistatic agent and water, and the solid content of the sizing liquid is 7% to 13%.
[0014] The present invention also provides an aramid III / PTFE self-lubricating fabric grey cloth prepared by the preparation method described in the above scheme.
[0015] Preferably, the mass fraction of aramid III fiber in the aramid III / PTFE self-lubricating fabric grey cloth is 29% to 85%;
[0016] The square meter weight of the aramid III / PTFE self-lubricating fabric is 185 g / m 2 ~345g / m 2 .
[0017] The present invention also provides a method for preparing an aramid III / PTFE self-lubricating liner composite material, comprising the following steps:
[0018] The aramid III / PTFE self-lubricating fabric described in the above scheme is impregnated in a resin solution to obtain a prepreg;
[0019] The prepreg is bonded to the surface of a metal substrate and then cured to obtain the aramid III / PTFE self-lubricating liner composite material.
[0020] Preferably, the metal substrate comprises titanium alloy or stainless steel;
[0021] The resin includes one or more of phenolic resin, polyimide resin and epoxy resin.
[0022] Preferably, the number of times of dipping is not less than 5 times; the aramid III / PTFE self-lubricating fabric grey cloth is cut before dipping, and the cutting direction is perpendicular to the distribution direction of the aramid III fibers in the fabric;
[0023] The bonding direction during bonding is perpendicular to the distribution direction of the aramid III fibers in the fabric;
[0024] The curing temperature is 130-200° C., the heat preservation time is 90-150 min, and the pressure is 0.1-5 MPa.
[0025] The present invention also provides an aramid III / PTFE self-lubricating liner composite material prepared by the preparation method described in the above scheme, comprising an aramid III / PTFE self-lubricating fabric grey cloth and a resin loaded in the aramid III / PTFE self-lubricating fabric grey cloth.
[0026] The present invention also provides the use of the aramid III / PTFE self-lubricating fabric grey cloth described in the above scheme or the aramid III / PTFE self-lubricating pad composite material described in the above scheme in frictional moving parts.
[0027] The invention provides a method for preparing an aramid III / PTFE self-lubricating fabric, comprising the following steps: using aramid III fiber filaments and polytetrafluoroethylene fiber filaments as raw materials for weaving to obtain the aramid III / PTFE self-lubricating fabric; the tissue cycle number of the aramid III / PTFE self-lubricating fabric is R, wherein 4≤R≤8; the tissue point flying number of the aramid III / PTFE self-lubricating fabric is S, wherein -(R-1)≤S≤+(R-1); the warp flying number of the aramid III / PTFE self-lubricating fabric is S. j , the number of latitudinal flights is S w , where |S j |≥|S w |. The three original weaves (i.e. plain weave, twill weave and satin weave) are characterized by a small number of fabric weave cycles and a uniform distribution of fabric weave points. The present invention, based on the theory of textile structure, breaks the limitation of the original weave cycle number, adjusts the weave cycle number and the weave point flying number, adjusts the distribution and repetition law of the warp and weft yarns, increases the proportion of self-lubricating fibers (i.e. polytetrafluoroethylene fibers) and reinforcing fibers (i.e. aramid III fibers) in the same cycle, improves the inherent defects of the original weave, and makes the distribution of fiber materials in the fabric different from that of conventional fabrics used in self-lubricating pads. The obtained new fabric has high bearing capacity, good friction and wear resistance, and good adhesion to different metal materials.
[0028] The present invention also provides a method for preparing an aramid III / PTFE self-lubricating gasket composite material, wherein the aramid III / PTFE self-lubricating fabric blank described in the above scheme is impregnated in a resin liquid to obtain a prepreg; the prepreg is bonded to the surface of a metal substrate and then cured to obtain the aramid III / PTFE self-lubricating gasket composite material. The aramid III / PTFE self-lubricating gasket composite material prepared by the present invention has high bearing capacity and good friction and wear performance, and is suitable for high-frequency friction conditions. The results of the examples show that the aramid III / PTFE self-lubricating gasket composite material of the present invention can maintain a low friction coefficient and a small wear scar depth when the sliding speed is 800r / min and the load is 15 to 37.5MPa. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing an aramid III / PTFE self-lubricating fabric, comprising the following steps:
[0030] Aramid III fiber filaments and polytetrafluoroethylene fiber filaments are used as raw materials for weaving to obtain the aramid III / PTFE self-lubricating fabric grey cloth;
[0031] The number of tissue cycles of the aramid III / PTFE self-lubricating fabric is R, wherein 4≤R≤8;
[0032] The tissue point flying number of the aramid III / PTFE self-lubricating fabric is S, wherein -(R-1)≤S≤+(R-1);
[0033] The warp number of the aramid III / PTFE self-lubricating fabric is S j , the number of latitudinal flights is S w , where |S j |≥|S w |.
[0034] In the present invention, the aramid III fiber filaments can be used as warp yarns or as weft yarns, and the present invention does not make specific limitations. Specifically, when the aramid III fiber filaments are used as warp yarns, the polytetrafluoroethylene (PTFE) fiber filaments are used as weft yarns, and when the aramid III fiber filaments are used as weft yarns, the PTFE fiber filaments are used as warp yarns.
[0035] In the present invention, the value of R is 4, 5, 6, 7 or 8, and the value range of the tissue point flying number S is selected according to the value of R. Specifically, when R is 4, then -3≤S≤+3, specifically -3, -2, -1, 1, 2 or 3; when R is 5, then -4≤S≤+4, specifically -4, -3, -2, -1, 1, 2, 3 or 4; when R is 6, then -5≤S≤+5, specifically The number of flights in the longitudinal direction can be -5, -4, -3, -2, -1, 1, 2, 3, 4 or 5; when R is 7, then -6≤S≤+6, specifically -6, -5, -4, -3, -2, -1, 1, 2, 3, 4, 5 or 6; when R is 8, then -7≤S≤+7, specifically -7, -6, -4, -3, -2, -1, 1, 2, 3, 4, 5 or 6; in the present invention, the number of flights in the longitudinal direction S j and the latitudinal flight number S w All must meet the requirement of -(R-1)≤S≤+(R-1).
[0036] In a specific embodiment of the present invention, the number of weaving points on a warp yarn is preferably not less than 2, specifically 2 to 4, and the number of weaving points on a weft yarn is preferably not less than 2, specifically 2 to 4; in a specific embodiment of the present invention, the number of flying points between two adjacent weaving points on the warp yarn or the weft yarn can be a variable, for example, S j Can be +3, +1, S w +1, +1, that is, according to S j +3, +1 are set alternately, S w Set as +1; or S j Can be -3, -1, S w = -1, -1, that is, according to S j The regular setting of -3 and -1 is repeated. S w Set it as -1.
[0037] In the present invention, |S j |≥|S w |, the present invention controls the value of the warp flying number to be greater than or equal to the weft flying number, which can highlight the distribution of the warp direction fibers in the fabric (similarly, the back of the fabric highlights the distribution of the weft direction fibers), which is beneficial to improving the reasonable distribution of the reinforcing fibers and lubricating fibers in the warp and weft directions of the fabric.
[0038] In the present invention, the weave points and the weave point flying number are integrated in the warp and weft directions. On a warp yarn, the weave points are staggered on the warp yarn according to the design; similarly, on a weft yarn, the first weave point is consistent with the interlaced warp yarn, and the second and the weave points in the loop are staggered on the weft yarn according to the design. The calculation of the fabric structure weave loop number is obtained by adding the weave points on the warp / weft yarns. The remaining warp yarns and weft yarns in the loop form interlacing points in sequence with the previous yarn according to the direction of the weave point flying number and the size of the weave point.
[0039] In the present invention, the number of tissue point flying S and the number of tissue cycles R are important parameters constituting the fabric structure. The number of tissue cycles and the distribution of tissue points in the fabric structure determine the repetition range and distribution of fibers in the fabric. The stress concentration around the tissue points (interweaving points) in the fabric can promote the initiation and expansion of damage, and the distribution of tissue points is determined by the size and direction of the number of tissue point flying, and the size of the number of tissue cycle constrains the size of the number of tissue point flying. The characteristics of the three original structures (i.e., plain weave, twill and satin weave) are that the number of fabric tissue cycles is small, the fabric tissue points are distributed in the same state, and the number of tissue point flying is unique and unchanged. The number of fabric cycles of the original structure is small, and within a certain length range, the number of fabric cycles of the original structure is repeated more. The reinforcement method of the fabric is often to increase the bearing capacity of the fiber by increasing a single reinforcing fiber, but due to the small number of fabric cycles, the increase in the reinforcing fiber is also limited, and then the bearing capacity of the resulting fabric is small; secondly, the number of original fabric tissue cycles is small, and the proportion of lubricating fibers appearing in one cycle is also small, so its friction and wear resistance effect will also be relatively poor. The present invention breaks the limitation of the original tissue cycle number and controls the tissue cycle number within the range of 4 to 8. By regulating the tissue point flying number, the distribution and repetition pattern of the warp and weft yarns are adjusted to achieve the corresponding effect in a specific direction. The final fabric not only has good load-bearing capacity, but also has excellent friction and wear resistance.
[0040] In the present invention, the aramid III fiber filament is preferably a multifilament composed of 30 to 150 fiber monofilaments, specifically a multifilament composed of 30, 40, 50, 60, 80, 100, 120 or 150 fiber monofilaments; the linear density of the aramid III fiber filament is preferably 5tex to 92tex, specifically 10tex, 20tex, 23tex, 25tex, 40tex, 50tex, 60tex, 70tex or 80tex, and the tensile strength of the aramid III fiber filament is preferably greater than 20cN / dtex. In the present invention, the aramid III fiber filament has a small linear density, a small monofilament diameter, and a large monofilament specific surface area, and can absorb more glue, which is beneficial to improving the bonding performance between the pad and the fabric. In the present invention, the aramid III fiber filament is not specially treated before use, and the fiber raw yarn state is maintained. During weaving, 50 to 100 meters of the surface yarn of the yarn tube is wound, which cannot be used and is treated as waste yarn.
[0041] In the present invention, the PTFE fiber filament is preferably a multifilament composed of 10 to 100 fiber monofilaments, specifically a multifilament composed of 20, 30, 40, 50, 60, 80 or 100 fiber monofilaments; the linear density of the polytetrafluoroethylene fiber filament is preferably 10tex to 89tex, specifically 20tex, 23tex, 25tex, 40tex, 50tex, 60tex, 70tex or 80tex; the tensile strength of the PTFE fiber filament is preferably greater than 1.35cN / dtex. In a specific embodiment of the present invention, the yarn tube mass of the PTFE fiber filament is preferably greater than 1 kg, and there should be no hairy or broken yarns on the surface layer and the upper and lower ends of the yarn tube. The linear density deviation of the PTFE fiber filament is preferably less than 8%. The present invention adopts the PTFE fiber filaments with the above-mentioned linear density and tensile strength, which can control the fabric thickness and warp and weft density adjustment, which is beneficial to improve the mechanical properties and lubrication properties of the gasket.
[0042] In the present invention, the polytetrafluoroethylene fiber filament is preferably sized before weaving; the ingredients of the sizing slurry preferably include polyvinyl alcohol, an antistatic agent and water, and the solid content of the slurry is preferably 7% to 13%, specifically 8%, 10% or 12%; the content of the antistatic agent in the slurry is preferably 0.5 to 1.5%; the present invention has no special requirements for the type of the antistatic agent, and those familiar to those skilled in the art can be used. In the present invention, the preparation method of the slurry preferably includes: heating and mixing polyvinyl alcohol, an antistatic agent and water to obtain the slurry; the temperature of the heating and mixing is preferably 90 to 100°C, specifically 95°C, and the present invention has no special requirements for the time of the heating and mixing, as long as the raw materials can be completely dissolved. The present invention has no special requirements for the specific operation method of the sizing, and those familiar to those skilled in the art can be used.
[0043] In a specific embodiment of the present invention, the warp yarn is preferably warped before sizing, and after sizing, the warp yarn is passed through the reed, and the weft yarn is woven into the cloth mouth, and then weaving is performed; the present invention has no special requirements on the specific methods of warping and passing through the reed, and those familiar to those skilled in the art can be used; the loom used for weaving is preferably a shuttle loom, an air jet loom and a rapier loom. Specifically, when the aramid III fiber filament is used as the weft yarn, a rapier loom is preferably used.
[0044] After weaving, the present invention preferably washes and dries the obtained aramid III / PTFE self-lubricating fabric. The present invention has no requirements on the washing method and number of washing, as long as the surface impurities of the obtained fabric can be washed away; the drying is preferably oven drying or natural drying.
[0045] The present invention also provides an aramid III / PTFE self-lubricating fabric obtained by the preparation method described in the above scheme. In the present invention, the mass fraction of aramid III fiber in the aramid III / PTFE self-lubricating fabric is preferably 29% to 85%, specifically 30%, 35%, 40%, 60%, 70% or 80%; the square meter weight of the aramid III / PTFE self-lubricating fabric is preferably 185g / m 2 ~345g / m 2 , specifically 200g / m 2 , 250g / m 2 , 260g / m 2 , 280g / m 2 , 300g / m 2 or 340g / m 2 .
[0046] The present invention also provides an aramid III / PTFE self-lubricating pad composite material, comprising an aramid III / PTFE self-lubricating fabric grey cloth and a resin loaded in the aramid III / PTFE self-lubricating fabric grey cloth; the aramid III / PTFE self-lubricating fabric grey cloth is the aramid III / PTFE self-lubricating fabric grey cloth described in the above scheme.
[0047] The present invention also provides a method for preparing the aramid III / PTFE self-lubricating liner composite material described in the above scheme, comprising the following steps:
[0048] The aramid III / PTFE self-lubricating fabric is impregnated in a resin solution to obtain a prepreg;
[0049] The prepreg is bonded to the surface of a metal substrate and then cured to obtain the aramid III / PTFE self-lubricating liner composite material.
[0050] The present invention impregnates aramid III / PTFE self-lubricating fabric grey cloth in resin liquid to obtain prepreg. In the present invention, the aramid III / PTFE self-lubricating fabric grey cloth is preferably cut before impregnation, and the cutting direction is perpendicular to the distribution direction of the aramid III fiber in the fabric; the resin used in the resin liquid is preferably phenolic resin, and more preferably thermosetting phenolic resin; the resin liquid is preferably obtained by diluting the resin, and the diluent used for the dilution is preferably acetone, ethanol and ethyl acetate, and the volume ratio of acetone, ethanol and ethyl acetate is preferably 1:1:1; the solid content of the resin liquid is preferably 12% to 15%; the number of impregnations is preferably not less than 5 times, and more preferably 5 to 10 times, and specifically can be 5 times, 6 times, 7 times, 8 times or 9 times; the total impregnation amount of the impregnation is preferably increased by 30% to 35%; after impregnation, the material impregnated with the resin liquid is preferably dried to obtain the prepreg.
[0051] After obtaining the prepreg, the present invention bonds the prepreg to the surface of the metal substrate and then solidifies it to obtain the aramid III / PTFE self-lubricating liner composite material. In the present invention, the metal substrate preferably includes titanium alloy or stainless steel, the titanium alloy is preferably TC4 titanium alloy or 60NiTi alloy, and the stainless steel is preferably 17-4PH stainless steel; the bonding method is preferably: brushing glue on the surface of the prepreg and the metal substrate, and after the glue is solidified, bonding the glue-brushed surface of the prepreg and the glue-brushed surface of the metal substrate; the glue is the resin liquid used during impregnation; during the bonding, the side with aramid III fiber as the main part is bonded to the metal substrate; when the prepreg is bonded to the metal substrate, the glue on the surface of the metal substrate is uniform and dry; the bonding direction during the bonding is preferably perpendicular to the distribution direction of the aramid III fiber in the fabric. In the present invention, the peel strength in the direction of the aramid III fiber is 1 to 2 times the peel strength in the direction of the PFTE fiber. The present invention controls the cutting direction to ensure the bonding strength of the prepreg on the surface of the metal substrate. In the present invention, when the metal substrate is a metal block made of titanium alloy and the bonding and cutting direction of the fabric is perpendicular to the direction of the aramid III fiber, the minimum peel strength is 1.2N / mm; when the metal substrate is a metal block made of stainless steel and the bonding and cutting direction of the fabric is perpendicular to the direction of the aramid III fiber, the minimum peel strength is 1.1N / mm (AS81820 requires bearing bonding strength to be ≥0.35N / mm).
[0052] In the present invention, the curing temperature is preferably 130-200°C, specifically 150°C, 160°C, 180°C or 190°C; the curing insulation time is preferably 90-150min, specifically 100min, 120min or 130min; the curing pressure is preferably 0.1-5MPa, specifically 0.2MPa, 0.5MPa, 1MPa, 3MPa or 4MPa.
[0053] The present invention also provides the aramid III / PTFE self-lubricating pad composite material described in the above scheme or the use of the aramid III / PTFE self-lubricating pad composite material described in the above scheme in friction moving parts. The aramid III / PTFE self-lubricating pad composite material provided by the present invention is suitable for high-frequency friction working conditions.
[0054] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] The number of tissue cycles of the basic tissue is R = 8, and the number of warp flights is S j = +3, +1; weft flying number S w =+1, +1. PTFE fiber filaments with a linear density of 44.44tex are selected as warp yarns, and aramid III fiber filaments with a linear density of 23tex are selected as weft yarns. 2550 PTFE fiber filaments are taken for warping. After warping, sizing is performed. The sizing liquid is obtained by heating and mixing polyvinyl alcohol, antistatic agent (model D-120) and water. The heating temperature is 95°C, the solid content of the slurry is 10%, and the content of the antistatic agent is 1.5wt%; after sizing, the heald is passed through the reed, and the heald is passed through in a forward manner, with 8 yarns in one cycle, and 4 yarns are passed through the same reed eye. A fully automatic rapier loom is used, and 8 heald frames are selected to pass through the ground warp, and 2 heald frames are passed through the side healds. The warp yarns are arranged by the heald frames according to S j and S w The size and direction of the fabric are ups and downs, and the weft yarn is woven into the cloth to complete the weaving of the fabric. The resulting fabric surface density is 258±10g / m 2 .
[0057] After weaving is completed, the impurities on the surface of the fabric are washed off according to the conventional textile mode. After washing, the fabric is naturally dried. The drying environment temperature and humidity refer to the laboratory temperature specified in GB / T 6529.
[0058] The dried fabric was impregnated in a resin solution, and the selected resin was a phenolic resin (model 204). The cut fabric was 10 cm × 10 cm in size and weighed 2.60 g. The thermosetting phenolic resin was diluted with a diluent consisting of acetone, ethanol and ethyl acetate (the volume ratio of acetone, ethanol and ethyl acetate was 1:1:1). The diluted resin solution had a solid content of 15%. The fabric was dipped 7 times, and the weight after dipping was 3.47 g to obtain a prepreg.
[0059] The dried prepreg was cut into a size of 3.5 cm × 3.5 cm. After brushing glue on the 17-4PH stainless steel metal substrate and the prepreg surface, the prepreg was bonded to the surface of the 17-4PH stainless steel sample (the cutting direction and the bonding direction were both perpendicular to the distribution direction of the aramid III fiber in the fabric), and a pressure of 0.03 ± 0.01 MPa was applied. The prepreg was kept warm at 180 ± 10 ° C in a blast oven for 2.3 hours to obtain an aramid III / PTFE self-lubricating pad friction test piece.
[0060] The friction and wear test was carried out on the Xuanwu No. 3 bolt-disc friction tester, with the sliding speed of the bolt-disc being 800r / min, the applied load being 15Mpa, and the test time being 120min. At the end of the friction test, the average friction coefficient was 0.1157, and the wear scar depth was measured to be 0.01203mm using a digital depth gauge.
[0061] In addition, the peel strength of the aramid III / PTFE self-lubricating liner friction test piece was tested. The results showed that the warp peel strength was 1.15 N / mm and the weft peel strength was 1.21 N / mm.
[0062] Example 2
[0063] The aramid III / PTFE self-lubricating fabric grey cloth consistent with Example 1 was cut into 10×10 cm fabric, weighing 2.67 g. The diluted phenolic resin solution used was the same as that in Example 1, and the mass after 7 impregnations was 3.66 g, to obtain the aramid III / PTFE self-lubricating liner prepreg. The dried prepreg was cut into a size of 3.5 cm×3.5 cm and then bonded and cured. The bonding and curing process was consistent with Example 1, to obtain the aramid III / PTFE self-lubricating liner friction test piece.
[0064] The friction and wear test was carried out using the Xuanwu No. 3 bolt-disc friction tester, with the bolt-disc sliding speed of 800r / min, the applied load of 25MPa, and the test time of 120min. At the end of the friction test, the average friction coefficient was 0.0761, and the wear scar depth was 0.01741mm measured by a digital depth gauge.
[0065] Example 3
[0066] The number of fabric basic structure cycles is R=8, and the number of warp flies is S j =-3, -1, the number of latitudinal flights is S w =-1, -1. PTFE fiber filaments with a linear density of 44.44 tex were selected as warp yarns, and aramid III fiber filaments with a linear density of 23 tex were selected as weft yarns. 2616 PTFE fiber filaments were wound around as warp yarns, and sizing was performed after warping was completed. The sizing liquid used was the same as that in Example 1. After sizing, the heddle was passed through the reed. The heddle was passed through in a straight-through manner, with 8 yarns in one cycle, and 4 yarns were passed through the same reed eye. A fully automatic rapier loom was used, and the weaving method was the same as that in Example 1 to obtain aramid III / PTFE self-lubricating fabric.
[0067] The desized fabric was cut into 10×10 cm size and weighed 2.58 g. The diluted phenolic resin glue in Example 1 was used for impregnation, and the weight was 3.44 g after 7 impregnations. After impregnation, the dried prepreg was cut into 3.5 cm×3.5 cm size, and then bonded and cured with a 17-4PH stainless steel sample. The process conditions were the same as in Example 1 to obtain an aramid III / PTFE self-lubricating liner friction test piece.
[0068] The friction and wear test was carried out using the Xuanwu No. 3 bolt-disc friction tester, with the bolt-disc sliding speed of 800r / min, the applied load of 25Mpa, and the test time of 120min. At the end of the friction test, the average friction coefficient was 0.0608, and the wear scar depth was measured by a digital depth gauge to be 0.01427mm.
[0069] In addition, the peel strength of the aramid III / PTFE self-lubricating pad friction test piece was tested. The results showed that the warp peel strength was 1.12 N / mm and the weft peel strength was 1.21 N / mm.
[0070] Example 4
[0071] The aramid III / PTFE self-lubricating fabric grey cloth consistent with Example 3 was cut into 10×10 cm fabric, weighing 2.61 g, and the diluted resin solution consistent with Example 1 was used, and the weight was 3.52 g after impregnation 7 times. The dried prepreg was cut into 3.5 cm×3.5 cm size and then bonded and cured, and the same bonding and curing process as Example 1 was used to obtain the aramid III / PTFE self-lubricating pad friction test piece.
[0072] The friction and wear test was carried out using the Xuanwu No. 3 bolt-disc friction tester, with the bolt-disc sliding speed of 800r / min, the applied load of 37.5Mpa, and the test time of 120min. At the end of the friction test, the average friction coefficient was 0.0359, and the wear scar depth was measured by a digital depth gauge to be 0.00788mm.
[0073] Comparative Example 1
[0074] For comparison consistency, PTFE fiber filaments are still selected as warp yarns and aramid III fiber filaments are selected as weft yarns. The linear density of PTFE fiber filaments is 44.4tex, and the linear density of aramid III fiber filaments is 23tex. Ordinary three-primary weave fabrics are used. In order to highlight the importance of weave point flying number, 2 / 2 twill and 3 / 1 twill fabrics are selected. The twill direction is consistent with that of Example 1. The obtained fabrics are applied to subsequent comparative examples 2 to 4.
[0075] Comparative Example 2
[0076] The 2 / 2 twill friction test piece was prepared by using the same impregnation, bonding and curing process as in Example 1. The friction test was carried out on a Xuanwu No. 3 bolt-disc friction tester, with a bolt-disc sliding speed of 800 r / min, an applied load of 15 MPa, and a test time of 120 min. At the end of the friction test, the average friction coefficient was 0.1190, and the wear scar depth was 0.01412 mm measured by a digital depth gauge.
[0077] Comparative Example 3
[0078] The friction test piece was prepared using 2 / 2 twill fabric, and the preparation method was the same as that of comparative example 2. The friction and wear test was carried out on the Xuanwu No. 3 bolt-disc friction tester. The sliding speed of the bolt-disc was 800r / min, the applied load was 37.5Mpa, and the test time was 120min. At the end of the friction test, the average friction coefficient was 0.0718, and the wear scar depth was 0.02222mm measured by a digital depth gauge. Compared with Example 4, it can be seen that under the same friction conditions, the average friction coefficient of the self-lubricating pad obtained in Example 4 is smaller, and the wear scar depth is smaller, indicating that the self-lubricating pad of the present invention has better load-bearing capacity and friction and wear performance.
[0079] Comparative Example 4
[0080] The friction test piece was prepared using 3 / 1 twill fabric, and the preparation method was the same as that of comparative example 2. The friction and wear test was carried out on the Xuanwu No. 3 bolt-disc friction tester. The sliding speed of the bolt-disc was 800r / min, the applied load was 25Mpa, and the test time was 120min. At the end of the friction test, the average friction coefficient was 0.0817, and the wear scar depth was 0.04608mm measured by a digital depth gauge. By comparing with Example 2 and Example 3, it can be seen that under the same friction conditions, the average friction coefficient of the self-lubricating pads obtained in Example 2 and Example 3 is smaller, and the wear scar depth is smaller, indicating that the self-lubricating pad of the present invention has better load-bearing capacity and friction and wear performance.
[0081] It can be seen from the data of the above comparative examples that, compared with the three original fabrics, the new fabric obtained by the present invention has a stronger load-bearing capacity, more excellent friction and wear performance, and is suitable for high-frequency friction conditions.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an aramid III / PTFE self-lubricating fabric, characterized in that: The following steps are involved: Aramid III fiber filaments and polytetrafluoroethylene fiber filaments are used as raw materials for weaving to obtain the aramid III / PTFE self-lubricating fabric grey cloth; The number of tissue cycles of the aramid III / PTFE self-lubricating fabric is R, wherein 4≤R≤8; The tissue point flying number of the aramid III / PTFE self-lubricating fabric is S, wherein -(R-1)≤S≤+(R-1); The warp number of the aramid III / PTFE self-lubricating fabric is S j , the number of latitudinal flights is S w , where |S j |≥|S w |.
2. The preparation method according to claim 1, characterized in that: The aramid III fiber filament is a multifilament composed of 30 to 150 fiber monofilaments; the linear density of the aramid III fiber filament is 5 tex to 92 tex, and the tensile strength is greater than 20 cN / dtex; The polytetrafluoroethylene fiber filament is a multifilament composed of 10 to 100 fiber monofilaments; the linear density of the polytetrafluoroethylene fiber filament is 10 tex to 89 tex, and the tensile strength is greater than 1.35 cN / dtex.
3. The preparation method according to claim 1, characterized in that: The polytetrafluoroethylene fiber filaments are sized before weaving; the sizing liquid comprises polyvinyl alcohol, an antistatic agent and water, and the solid content of the sizing liquid is 7% to 13%.
4. Aramid III / PTFE self-lubricating fabric prepared by the preparation method according to any one of claims 1 to 3.
5. The aramid III / PTFE self-lubricating fabric according to claim 4, characterized in that: The mass fraction of aramid III fiber in the aramid III / PTFE self-lubricating fabric grey cloth is 29% to 85%; The square meter weight of the aramid III / PTFE self-lubricating fabric is 185 g / m 2 ~345g / m 2 .
6. A method for preparing an aramid III / PTFE self-lubricating liner composite material, characterized in that: The following steps are involved: The aramid III / PTFE self-lubricating fabric according to claim 4 or 5 is impregnated in a resin solution to obtain a prepreg; The prepreg is bonded to the surface of a metal substrate and then cured to obtain the aramid III / PTFE self-lubricating liner composite material.
7. The preparation method according to claim 6, characterized in that: The metal substrate includes titanium alloy or stainless steel; the resin includes one or more of phenolic resin, polyimide resin and epoxy resin.
8. The preparation method according to claim 6, characterized in that: The number of times of dipping is not less than 5 times; the aramid III / PTFE self-lubricating fabric grey cloth is cut before dipping, and the cutting direction is perpendicular to the distribution direction of the aramid III fibers in the fabric; The bonding direction during bonding is perpendicular to the distribution direction of the aramid III fibers in the fabric; The curing temperature is 130-200° C., the heat preservation time is 90-150 min, and the pressure is 0.1-5 MPa.
9. The aramid III / PTFE self-lubricating liner composite material prepared by the preparation method according to any one of claims 6 to 8, comprising an aramid III / PTFE self-lubricating fabric grey cloth and a resin loaded in the aramid III / PTFE self-lubricating fabric grey cloth.
10. Use of the aramid III / PTFE self-lubricating fabric grey cloth according to claim 4 or 5 or the aramid III / PTFE self-lubricating pad composite material according to claim 9 in frictional moving parts.